Free surfaces recast superconductivity in few-monolayer MgB2: Combined first-principles and ARPES demonstration. Issue 1 (December 2017) - Bekaert, J.; Bignardi, L.; Aperis, A.; van Abswoude, P.; Mattevi, C.; Gorovikov, S.; Petaccia, L.; Goldoni, A.; Partoens, B.; Oppeneer, P.; Peeters, F.; Milošević, M.; et al.
Abstract Two-dimensional materials are known to harbour properties very different from those of their bulk counterparts. Recent years have seen the rise of atomically thin superconductors, with a caveat that superconductivity is strongly depleted unless enhanced by specific substrates, intercalants or adatoms. Surprisingly, the role in superconductivity of electronic states originating from simple free surfaces of two-dimensional materials has remained elusive to date. Here, based on first-principles calculations, anisotropic Eliashberg theory, and angle-resolved photoemission spectroscopy (ARPES), we show that surface states in few-monolayer MgB2 make a major contribution to the superconducting gap spectrum and density of states, clearly distinct from the widely known, bulk-likeσ - andπ -gaps. As a proof of principle, we predict and measure the gap opening on the magnesium-based surface band up to a critical temperature as high as 30 K for merely six monolayers thick MgB2 . These findings establish free surfaces as an unavoidable ingredient in understanding and further tailoring of superconductivity in atomically thin materials.